2015
DOI: 10.21101/cejph.a4027
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare System Financing and Profits: All That Glitters is Not Gold

Abstract: SUMMARYThe objective of this paper is an analysis of two main attributes of healthcare systems. First of the main attributes is the trend of ever growing expenditures of healthcare systems all across the world. Second attribute is the efficiency of chosen mixed healthcare systems, where mixed system is one which features involvement of both private and public sector. Countries chosen for analysis are USA as the country with high private sector influence on healthcare, France with its mediocre influence and Jap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Another study reported growing expenditures of healthcare systems all over the world, including the CR. One of the basic factors of expenditure growth is the ageing of population (26). Important components in active ageing are personal active ageing strategies of older people, which include lower alcohol consumption (27).…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported growing expenditures of healthcare systems all over the world, including the CR. One of the basic factors of expenditure growth is the ageing of population (26). Important components in active ageing are personal active ageing strategies of older people, which include lower alcohol consumption (27).…”
Section: Discussionmentioning
confidence: 99%
“…Toxicity of many drugs in children is different to that observed in adults, and indeed, there are some groups of paediatric patients, such as neonates, in whom a higher toxicity is relatively common . The errors lead to high stress and upset children and parents, emergency calls and/or hospital admissions .…”
Section: Discussionmentioning
confidence: 99%
“…Within the European Union as well as the Organisation for Economic Co-operation and Development, significant differences in the availability of resources for mental healthcare are evident. Over the past three decades, the most common causes of death changed from infectious diseases to chronic diseases, putting further pressure on the efficiency and effectiveness of healthcare [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%